2015
DOI: 10.3390/ma8084679
|View full text |Cite
|
Sign up to set email alerts
|

Important Parameter Groups in Thermal Protection of Polymers

Abstract: The problem of thermal protection is explored for two idiosyncratic reactive systems, namely a sacrificial heat-sink material and an intumescent system where a dynamically evolving insulation layer is produced from an initially thin coating. Relatively simple mathematical models of both systems are proposed that encompass the important physical characteristics of each situation and these models are analysed using a mixture of numerical and analytical techniques. Important dimensionless parameter groups are ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Therefore, the ideal condition to have minimal total thermal conductivity is to have a large number of small pores. 70 Another criterion for the char layer to have minimal heat transfer rate is that the thermal diffusion time scale should be large. Hu et al 71 found that the thermal conductivity of low dielectric porous xerogel film drops much faster than linearity with an increase in porosity, which is explained using two porosity weighted semiempirical model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the ideal condition to have minimal total thermal conductivity is to have a large number of small pores. 70 Another criterion for the char layer to have minimal heat transfer rate is that the thermal diffusion time scale should be large. Hu et al 71 found that the thermal conductivity of low dielectric porous xerogel film drops much faster than linearity with an increase in porosity, which is explained using two porosity weighted semiempirical model.…”
Section: Resultsmentioning
confidence: 99%
“…During high temperature annealing, the degradation of carboxymethyl cellulose polymer shell at nanoparticles can dynamically form a porous char layer, where the porosity increases with annealing time and temperature. The total thermal conductivity λ T is given by where λ p is a parameter that depends on pore-specific variables, and T a is ambient temperature. For very small pores, λ p ≈ 4εσ T a 3 δ, where ε is the emissivity of the internal surface of the pore and σ is the Stefan–Boltzmann constant.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, these oxide layers are primarily used in high-value applications, such as gas turbine blades. A second, more novel type of TBC is a low-cost polymer-based film that intumesces to form a macroscale insulating layer when exposed to high temperatures. , The intumesced layer is porous, thus suppressing heat transfer by forcing thermal transport through the low thermal conductivity gas voids and polymer nanocomposite coating . These coatings are expendable, meant to protect the underlying substrate during extreme catastrophic events.…”
Section: Introductionmentioning
confidence: 99%
“…To the basic components of conventional intumescent coatings (ICs) belong (i) an inorganic acid or a compound releasing this acid during heating (mainly ammonium polyphosphate; APP), (ii) a carbon-rich substance allowing the formation of a char (pentaerythritol; PER) and (iii) a blowing agent facilitating foaming of the entire system (melamine, MEL). The char-forming process is much more complicated than the simple chemical reactions occurring between the main components; the process is the result of simultaneously charring and foaming of the coating surface [ 2 , 3 , 4 , 5 , 6 ]. The resulting char is an insulating layer that slows the heat and mass transfer between the gas and the condensed phase.…”
Section: Introductionmentioning
confidence: 99%